Ảnh hưởng của cổ đông lớn đến sự đồng biến động giá cổ phiếu trên Sở Giao dịch Chứng khoán Thành phố Hồ Chí Minh - Dang Tung , Lam (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2016)
This study aims to investigate the effect of large shareholders on stock price synchronicity. By using a comprehensive data set for all stocks listed on Hochiminh Stock Exchange (HOSE) from 2007 to 2014 and panel regression analyses, the results suggest that large shareholders have negative impact on stock price synchronicity, which is consistent with the argument that large shareholders contribute to improving the informativeness of stock prices and thus reducing the extent to which stock prices co-move.